2016
DOI: 10.1016/j.jagp.2016.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Health, Social, and Economic Variables Associated with Depression Among Older People in Low and Middle Income Countries: World Health Organization Study on Global AGEing and Adult Health

Abstract: Objective: Although depression among older people is an important public health problem worldwide, systematic studies evaluating its prevalence and determinants in low and middle income countries (LMICs) are sparse. Biopsychosocial model of depression and prevailing socioeconomic hardships for older people in LMICs have provided the impetus to determine the prevalence of geriatric depression, to study its associations with health, social, and economic variables, and to investigate socioeconomic inequalities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 48 publications
5
75
1
Order By: Relevance
“… 45 However, another study in LMICs revealed a negative association between medical insurance and depression. 46 Medical insurance may influence health through various channels. A lack of medical insurance limits access to preventive services.…”
Section: Discussionmentioning
confidence: 99%
“… 45 However, another study in LMICs revealed a negative association between medical insurance and depression. 46 Medical insurance may influence health through various channels. A lack of medical insurance limits access to preventive services.…”
Section: Discussionmentioning
confidence: 99%
“…The mean GDS-15 score was 4.43 (95% CI :4.11-4.78, SD ±2.87, range 0-13). Among all the positively screened patients (n=128), 104 (81.3%, 95% CI:73.4-87.6) screened positive for mild depression (score [5][6][7][8] and 24 (18.8%, 95% CI:12.4-26.6) were screened positive for severe depression (score >8) ( Table 1). When GDS-5 was used as the screening tool with a cutoff score of 2/3, 103 (36.8%, 95% CI:31.1-42.7) screened positive for depression with mean score of 1.3 (95% CI:1.16-1.43, SD ±1.146, Range 0-5) (Table2).…”
Section: Resultsmentioning
confidence: 99%
“…Nepal is one of the world's poorest countries, and considered a fragile state by the World Bank [6]. The WHO Study on Global AGEing and Adult Health (SAGE) identi ed depression in LMICs to be 4.7% [7]. However, in Nepal, from 17.3% to 89.1% of elders in elder care homes, 25.5%-60.6% of elders living in the community, and 53.2% to 57.1% of elders in hospitals suffer from depression [8].…”
Section: Introductionmentioning
confidence: 99%
“…As people age, the environment plays an increasingly important role and defines whether and to what degree an individual participates in social interaction, community engagement and physical activity 98 . Accordingly, geriatric depression is triggered by social and economic variables 99 . Research has found a strong correlation between social participation and positive health status in elderly among different communities in North America, Asia and Europe 96 .…”
Section: Social Cohesionmentioning
confidence: 99%